Le tourisme : un luxe réinventé ? - Yolanda Onghena (Études Caribéennes)
Talking about tourism is talking about dreams and illusions but also about ambiguities and constraints. On one side there are the expectations of tourists looking for authentic experiences and on the other, on the part of the local population, the impression of an unbalanced and unequal experience. The result can be discomfort experienced by some and frustrating experiences for others; or rather stay in a simple artificial recreation by the ones for the others in the service of a mode or a globalised pattern. In order to talk about this change of paradigm for understanding tourism in the actuality and analyse the degree of interaction between persons, we propose the concept of luxury as sign of differentiation, which draws closer to what happens between, on and with all the participants in the interaction. We will focus on opportunities for mobility and communication that globalization processes set in motion. Where tourism provides a real interaction between people and intercultural dialogue between subjects? How changes in behaviour cause changes in demand and tourism experience?